2022
DOI: 10.25133/jpssv302022.023
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Discriminatory Attitudes Towards People Living with HIV Among Women of Reproductive Age in Nepal: A Trend Analysis From National Surveys

Abstract: This study examines the effect of education and mass media on discriminatory attitudes towards people living with HIV (PLHIV) among women in Nepal. Data were drawn from the Nepal Demographic and Health Surveys 2006, 2011, and 2016 and covered 36,329 women of reproductive age (WRA) 15–49 years. An example of discriminatory attitude towards PLHIV is not wanting to buy fresh vegetables from a shopkeeper or vendor if an individual knew that the seller had HIV. Discriminatory attitude toward PLHIV has increased sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Several factors, including their education level, age, and exposure to relevant information, according to studies, influence individuals' knowledge and attitude toward HIV/AIDS, for instance, the Olugbenga-Bello study in Nigeria indicated that men with greater education levels had more chances to understand HIV/AIDS formally (Zhang et al, 2022). Concludes that men who had media exposure to the material of HIV/AIDS had more chances to have proper situation awareness (Acharya et al, 2022).…”
Section: Introduction 1acquiredmentioning
confidence: 99%
“…Several factors, including their education level, age, and exposure to relevant information, according to studies, influence individuals' knowledge and attitude toward HIV/AIDS, for instance, the Olugbenga-Bello study in Nigeria indicated that men with greater education levels had more chances to understand HIV/AIDS formally (Zhang et al, 2022). Concludes that men who had media exposure to the material of HIV/AIDS had more chances to have proper situation awareness (Acharya et al, 2022).…”
Section: Introduction 1acquiredmentioning
confidence: 99%